Profile of Teachers’ Instructional Actions in Project-Based Learning at Min 2 Samarinda - Zaitun Erniwati; Sunardi Sunardi; Puryati Puryati (Jurnal Impresi Indonesia, 2026)
The quality of education in the 21st century is largely determined by teachers' ability to implement innovative, student-centered learning models that align with modern competency demands. In this context, Project-Based Learning (PjBL) has emerged as one of the most relevant approaches for fostering critical thinking, creativity, and collaboration among students. This study describes teachers’ instructional actions in implementing PjBL at MIN 2 Samarinda, including planning, implementation, evaluation, and learning effectiveness. The method was descriptive qualitative, employing interviews, observations, and documentation with thematic analysis and triangulation. The results showed that teachers were able to design contextual learning objectives, flexible project steps, and relevant media. In implementation, teachers acted as facilitators and mentors through active guidance, group work, and simple technology. Evaluation was conducted using objective rubrics, feedback, and student reflection. However, two PjBL syntax stages—namely, planning, determining fundamental questions, and preparing project schedules—were not fully optimal. Overall, teachers' instructional actions effectively facilitated collaboration, motivation, and assessment of learning outcomes.